In Vivo Neural Interfaces—From Small- to Large-Scale Recording - Zhang, Bingjie; Deng, Chunshan; Cai, Chunzhi; Li, Xiaojian (Frontiers in Nanotechnology, 2022)
Brain functions arise from the coordinated activation of neuronal assemblies distributed across multiple brain regions. The electrical potential from the neuron captured by the electrode can be processed to extract brain information. A large number of densely and simultaneously recorded neuronal potential signals from neurons spanning multiple brain regions contributes the insight of specific behaviors encoded by the neural ensembles. In this review we focus on the neural interfaces developed for small to large scale recordings, and discuss the development challenges and strategies in micro-system, electrode device and interface material levels for the future larger scale neural ensemble recordings.